2015
DOI: 10.1016/j.chom.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

STING Activation by Translocation from the ER Is Associated with Infection and Autoinflammatory Disease

Abstract: SUMMARY STING is an ER-associated membrane protein that is critical for innate-immune sensing of pathogens. STING-mediated activation of the IFN-I pathway through the TBK1/IRF3 signaling axis involves both cyclic-dinucleotide binding, and its translocation from the ER to vesicles. However, how these events are coordinated, and the exact mechanism of STING activation, remain poorly understood. Here, we found that the Shigella effector protein IpaJ potently inhibits STING signaling by blocking its translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
407
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 475 publications
(449 citation statements)
references
References 28 publications
18
407
0
Order By: Relevance
“…We recently showed that pharmacological inhibition of TBK1 ameliorates disease phenotypes in Trex1 −/− mice (21). STING activation involves trafficking from the ER to cytoplasmic vesicles through the secretory pathway (13), during which time TBK1 is recruited and travels with STING as part of the STING signalsome, which is potentially targeted to lysosomes for degradation to prevent excessive IFN response (22) (see the model in Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that pharmacological inhibition of TBK1 ameliorates disease phenotypes in Trex1 −/− mice (21). STING activation involves trafficking from the ER to cytoplasmic vesicles through the secretory pathway (13), during which time TBK1 is recruited and travels with STING as part of the STING signalsome, which is potentially targeted to lysosomes for degradation to prevent excessive IFN response (22) (see the model in Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that TBK1 interacts with mTORC1 and inhibits its activity in prostate cancer cells (12). In the case of DNA sensing, STING recruits TBK1 to form the "STING signalsome" as soon as it exits the ER, and both proteins travel through the secretory pathway, potentially reaching lysosomes where mTORC1 is located (13). To test this possibility, we first knocked down TBK1 in WT and Trex1 −/− cells using four independent siRNAs.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the regulated trafficking of signaling molecules is underscored by the findings that Shigella inhibits STING signaling by blocking its translocation from the ER to ERGIC and that the ERGIC/Golgi trafficking mechanism of STING is deregulated in genetic autoinflammatory diseases (14). Our work demonstrates that the transport of BTN3A1-mediated TBK1 to the perinuclear region is critical for the induction of IFN-β gene expression in response to nucleic acid stimulation.…”
Section: Discussionmentioning
confidence: 78%
“…STING-mediated TBK1/IRF3 is fully activated at the ER-Golgi intermediate compartment (ERGIC) (14). STING, TBK1, and IRF3, all essential components for inducing type I IFN signaling, have been shown to translocate to these punctate structures, although the mechanism responsible for the dynamic trafficking of such molecules is unknown.…”
mentioning
confidence: 99%